Oligoasthenoteratozoospermia After Trial of Testicular Salvaging Surgery in Testicular Torsion: A Case Report - Mahfuz, Muhammad Ainul; Suwanto; Krisna, Muhammad Sidharta (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Testicular torsion (TT) is an emergency in urology that happens because of the spermatic cord’s rotation. Decreased of overall sperm parameters after TT often happens in which can endanger the patient’s fertility status. Approach on how to salvage the testicle and to prevent unwanted complications remains as the doctor’s greatest priority. We report a case of oligoasthenoteratozoospermia after surgical detorsion without orchidectomy in testicular torsion. A 19-year-old male, presenting with sudden, progressive, and continuous pain in the right testicle for 4 hours. The right testicle was larger in volume on physical examination, there were a negative phren sign and negative cremasteric reflex. Gray scale ultrasound without Doppler showed changes suggestive of testicular torsion. Emergency surgery revealed a dark-bluish right testicle with a 360o rotation of the spermatic cord. Detorsion without orchidectomy was performed with clinical judgment hoping for the restoration of testicular viability. Sperm analysis was done after one month and oligoasthenoteratozoospermia was found. Although some patients experience decreased overall sperm parameters after TT that perhaps making them infertile, interestingly there is no difference in pregnancy rates among couples with TT men when compared to the general population. The best testicular salvage surgery method to prevent testicular atrophy also has not been determined yet. Thus, the patient should be carefully counseled about the good outcome of pregnancy rate and the chance for testicular atrophy, regardless of what is the surgical choice.